Neural stem cell-mediated delivery of oncolytic adenovirus - Kim, Julius W. (Curr Protoc Hum Genet, 2015)
The use of stem cells (SCs) as carriers for therapeutic agents has by now progressed to early clinical trials. These clinical trials exploring SC-mediated delivery of oncolytic adenoviruses will commence in the near future, hopefully yielding meritorious results that could provoke further scientific inquiry. Preclinical animal studies have demonstrated that SCs can be successfully loaded with conditionally-replicative adenoviruses and, then, delivered to the tumor, upon which they may evoke pronounced therapeutic efficacy in the animal (Ahmed et al., 2011; Ahmed et al., 2012; Thaci et al., 2012; Tobias et al., 2013). Here in this protocol, we describe the maintenance of SCs, provide an analysis of optimal adenoviral titers for SC loading, and evaluate the optimized viral loading on SCs.